2011
DOI: 10.1073/pnas.1107811108
|View full text |Cite
|
Sign up to set email alerts
|

A single conformational transglutaminase 2 epitope contributed by three domains is critical for celiac antibody binding and effects

Abstract: The multifunctional, protein cross-linking transglutaminase 2 (TG2) is the main autoantigen in celiac disease, an autoimmune disorder with defined etiology. Glutamine-rich gliadin peptides from ingested cereals, after their deamidation by TG2, induce T-lymphocyte activation accompanied by autoantibody production against TG2 in 1-2% of the population. The pathogenic role and exact binding properties of these antibodies to TG2 are still unclear. Here we show that antibodies from different celiac patients target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 38 publications
8
61
0
Order By: Relevance
“…Interestingly, the immunodominant B-cell epitopes were highly similar to recently elucidated immunodominant T-cell epitopes (27). We did not observe linear B-cell epitopes derived from the CD-specific autoantigen TG2, which is consistent with the proposed existence of immundominant structural epitopes within TG2 (28). However, we cannot rule out the possibility that lower-abundance linear epitopes or structural mimotopes were enriched during library screening but outcompeted by DGP and D S / T FV Y / F Q peptides.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the immunodominant B-cell epitopes were highly similar to recently elucidated immunodominant T-cell epitopes (27). We did not observe linear B-cell epitopes derived from the CD-specific autoantigen TG2, which is consistent with the proposed existence of immundominant structural epitopes within TG2 (28). However, we cannot rule out the possibility that lower-abundance linear epitopes or structural mimotopes were enriched during library screening but outcompeted by DGP and D S / T FV Y / F Q peptides.…”
Section: Discussionsupporting
confidence: 73%
“…We previously reported that epitope 2 can be disrupted by introduction of the triple mutation R19S E153S M659S (30). This triple mutation was first described by SimonVecsei et al, who showed that it inhibits the binding of serum antibodies from celiac disease patients (31). Of the residues that were mutated in the previous study, Arg19 is located within the peptide we identified as an epitope-2 candidate by HDX-MS. We therefore tested the effect of the R19S mutation on mAb 2Q3Z) and the closed conformation (PDB ID code 1KV3) crystal structure, containing bound peptide inhibitor and GDP, respectively (bound molecules are shown in red stick representation).…”
Section: Disulfide Bond Formation In Itg2 Prevents the Stabilizing Efmentioning
confidence: 99%
“…Several factors might account for this difference. Firstly, the current study was performed by injecting TG2-specific autoantibodies targeting a single previously identified classical coeliac epitope, while autoantibodies against an additional three major TG2-epitopes also exist in coeliac patients (Iversen et al 2013;Simon-Vecsei et al 2012). Secondly, even though not reported, DGP-antibodies were found in the majority of the mice injected with coeliac patient-derived sera or immunoglobulins in the previous study, and also other antibody populations in addition to the TG2-antibodies were very likely present in the injections.…”
Section: Discussionmentioning
confidence: 99%